Angular momentum, accretion, and radial flows in chemodynamical models of spiral galaxies. Issue 8 (30th September 2016) - Pezzulli, G.; Fraternali, F.
Abstract: Gas accretion and radial flows are key ingredients of the chemical evolution of spiral galaxies. They are also tightly linked to each other (accretion drives radial flows due to angular momentum conservation) and should therefore be modeled simultaneously. We summarize an algorithm that can be used to consistently compute accretion profiles, radial flows, and abundance gradients under quite general conditions, and we describe illustrative applications to the Milky Way. We find that gas‐phase abundance gradients strongly depend on the angular momentum of the accreting material and, in the outer regions, they are significantly affected by the choice of boundary conditions.